Nurses' knowledge of evidence‐based guidelines on the prevention of peripheral venous catheter‐related infections: a multicentre survey. Issue 17 (20th December 2013) - Cicolini, Giancarlo; Simonetti, Valentina; Comparcini, Dania; Labeau, Sonia; Blot, Stijn; Pelusi, Gilda; Di Giovanni, Pamela
<x xml:space="preserve">Abstract</x> Aims and objectives To evaluate nurses' knowledge of guidelines for preventing infections associated with peripheral venous catheters. Background Guidelines for the prevention of intravascular catheter‐related infections are an important tool to help healthcare professionals minimise the risk of infection. However, they are not always applied by nurses. The literature on this topic is limited, and no study examined this matter for peripheral venous catheters. Design This cross‐sectional study was carried out from November 2011–June 2012. Methods The nurses' knowledge of peripheral venous catheter guidelines and its association with gender, experience, education and the ward membership was assessed using a validated questionnaire. Results Sixteen hospitals from six regions of Italy participated, and 933 questionnaires were collected. Most participants were female (70·1%), undergraduate (51·8%), worked in medical (35·8%) and surgical departments (28·0%), and had >10 years of experience (55·0%). The median score on 10 questions was 6 of 10. A majority of nurses knew it is recommended to replace peripheral venous catheters routinely (90·0%), to perform an aseptic technique during connecting/disconnecting the infusive lines (55·2%), and to replace the administration set <24 hour when lipid emulsions have been infused (88·4%). Of note, 52·6% of nurses advocated the use of steel needles, a potentially dangerous practice. In multivariate analysis, a higher level of education and the area of work were associated with better test scores. Conclusion The sample of nurses' knowledge to some recommendations is frequently low. This could be a potential risk factor for patient safety. The results should sensitise healthcare managers to improve nursing training and education, according to clinical risk management perspectives. Relevance to clinical practice These data request for more emphasis on international guidelines in infection prevention initiatives.